1998
DOI: 10.1149/1.1838304
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance Effect in Co‐Ag and Co‐Cu Alloy Films Prepared by Electrodeposition

Abstract: Thin films of Co-Ag, Co-Cu, and Fe-Cu alloys were produced by electrochemical deposition. In this study the relationship between the magnetoresistance (MR) ratio and the crystalline state in the electrodeposited alloy films is investigated. Even though for the Co-Ag system it is difficult to form a solid solution, precipitation of phase-separated fine particles or grains is relatively straightforward. It was found that the Co grain (or particle) size becomes smaller with increasing current density (1-10 mA/cm2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 1 publication
1
42
2
Order By: Relevance
“…The granular alloy thin films are immiscible combinations usually prepared by physical deposition methods [2,3]. Recently, electrochemical deposition is widely used to produce multilayered alloys exhibiting GMR [4][5][6][7]. This technique is preferred in low-end applications such as GMR sensors in automotive applications or in microsystems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The granular alloy thin films are immiscible combinations usually prepared by physical deposition methods [2,3]. Recently, electrochemical deposition is widely used to produce multilayered alloys exhibiting GMR [4][5][6][7]. This technique is preferred in low-end applications such as GMR sensors in automotive applications or in microsystems [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [35] reported room temperature MR of 0.5 % for the as-deposited Co-Au alloys and of up to 1.5 % when annealed at 573 K. They found that the grain size of Co increased with the increase of annealing temperature. Previous studies [37], [38] have shown GMR values of up to 4 % for the as-deposited Co/Au multilayers prepared using pulsed-current electrodeposition in the cyanide solution and demonstrated how closely GMR and magnetic properties are correlated with the layer thickness and composition in the as-deposited Co/Ag and Co/Cu nanostructures [38], [39]. However, it is not yet fully clear to what extent deposition current density, annealing, and layer thickness have an effect on the grain size and on the electrical and magnetic properties of Co-Au alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the formation of ferromagnetic clusters embedded in a nonmagnetic and conductive matrix makes this system interesting, especially in applications based on giant magnetoresistance (GMR; Berkowitz et al, 1992;Xiao et al, 1992). By contrast, electrodeposition is a good technique to produce Co-Cu solid solutions where Cu atoms substitute Co sites, forming a real alloy (Zaman et al, 1998;Bakkaloglu et al, 1998). The addition of Cu distorts the Co lattice parameters, strongly affecting the magnetic properties of the material and becoming an additional tool to tune the overall magnetic behavior of magnetic nanowire arrays (Karaagac et al, 2010;Kashi et al, 2011;Yang et al, 2011a,b).…”
Section: Co-cu Nanowiresmentioning
confidence: 99%